Planting conditions can enhance the bioactivity of mulberry by affecting its composition - Bai, Huixin; Jiang, Shanfeng; Liu, Jincai; Tian, Ye; Zheng, Xiaohui; Wang, Siwang; Xie, Yanhua; Li, Yao; Jia, Pu (Frontiers in Plant Science, 2023)
Mulberry (Morus alba L.) has a very special significance in the history of agriculture and economic plant cultivation. Mulberry has strong environmental adaptability, wide planting range and abundant output. It is not only an important supply for silkworm breeding, but also a raw material for various foods, and has a great potential for the development of biological resources. The bioactivities of mulberry in different planting areas are not the same, which becomes an obstacle to the development of mulberry. This is the first time to find that the variation of precipitation and temperature difference in planting areas will change the bias of mulberry biological activity through mathematical analysis. After studying mulberry samples from 12 planting areas in China, it was found that planting conditions with small temperature difference could affect the anti-apoptotic effect of the mulberry branch by changing the contents and proportion of rutin, hyperoside, and morisin. Adequate irrigation can promote the antioxidation of the mulberry branch by changing the contents and proportion of scopoletin and quercitrin. The results of analysis on planting conditions, contents of active components and their bioactivities correlation provide data support for improving mulberry planting conditions, and have guide significance for rational development of mulberry resources.